STRATEGI PEMASARAN DIGITAL PADA ONLINE SHOP IMPORTIR DI MARKETPLACE SHOPEE INDONESIA (Fenomenologi Pada Online Shop Universals) - Arianti Setiawan (2023)
Universals is an online shop that focuses on selling fashion products, including rubber sandals and clothing, imported from Thailand under the brand name Kito. This study elucidates the background of Universals' establishment as an online shop importer on the Shopee Indonesia platform, led by Michael Christian. Initially serving as a parcel forwarding service, Universals later built its own online shop to reduce expenses. Employing a qualitative phenomenological approach and conducting in-depth interviews, the research reveals that Universals has successfully leveraged digital marketing through Shopee Ads and S.T.P. segmentation analysis. However, it has been hesitant to expand its marketing efforts to other media channels. The findings demonstrate that the online shop's marketing strategies align with insights from various experts in the digital marketing field, yet there is room for growth in exploring additional marketing avenues.